2014
DOI: 10.1371/journal.pone.0110875
|View full text |Cite
|
Sign up to set email alerts
|

Glucolipotoxicity Impairs Ceramide Flow from the Endoplasmic Reticulum to the Golgi Apparatus in INS-1 β-Cells

Abstract: Accumulating evidence suggests that glucolipotoxicity, arising from the combined actions of elevated glucose and free fatty acid levels, acts as a key pathogenic component in type II diabetes, contributing to β-cell dysfunction and death. Endoplasmic reticulum (ER) stress is among the molecular pathways and regulators involved in these negative effects, and ceramide accumulation due to glucolipotoxicity can be associated with the induction of ER stress. Increased levels of ceramide in ER may be due to enhanced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…Beyond its primary function to deliver ceramide from the ER to the Golgi apparatus, CERT participates in various biological events, including polyploid cancer cell death 32 , EGF receptor signaling 33 , lipotoxicity and glucolipotoxicity in islet β-cells 34,35 , muscle insulin signaling 36 , stress-induced Golgi disassembly 37 , protein secretions 38 , phosphoinositide turnover at the trans Golgi network 39 , cytotoxic autophagy 40 , and senescence 41 . Additionally, pharmacological or genetic inhibition of CERT negatively affects the proliferation of several types of intracellular pathogens [42][43][44][45][46] .…”
Section: Discussionmentioning
confidence: 99%
“…Beyond its primary function to deliver ceramide from the ER to the Golgi apparatus, CERT participates in various biological events, including polyploid cancer cell death 32 , EGF receptor signaling 33 , lipotoxicity and glucolipotoxicity in islet β-cells 34,35 , muscle insulin signaling 36 , stress-induced Golgi disassembly 37 , protein secretions 38 , phosphoinositide turnover at the trans Golgi network 39 , cytotoxic autophagy 40 , and senescence 41 . Additionally, pharmacological or genetic inhibition of CERT negatively affects the proliferation of several types of intracellular pathogens [42][43][44][45][46] .…”
Section: Discussionmentioning
confidence: 99%
“…The increase of apoB100 expression by HFrD was mediated by reduced mRNA expression of hepatic PPAR (108). Increasing PPAR activity by promoting the accumulation of ceramide in the ER and lipotoxicity through ER stress (73). Palmitate-induced lipotoxicity can also be caused by altered phospholipid composition and consequent changes in membrane rigidity and fluidity (74), which are known to induce UPR signaling (75,76).…”
Section: Er Stress and Lipotoxicity In Peripheral Organsmentioning
confidence: 99%
“…The ELOVL2/DHA axis did not regulate ceramide and neutral lipid metabolism in INS-1 beta cells under conditions of glucolipotoxicity We previously showed that palmitate stimulates ceramide accumulation in beta cells either by increasing de novo synthesis [20] or by modulating ceramide metabolism [25]. We found that DL-threo-1-phenyl-2-palmitoylamino-3-morpholino-1-propanol (PPMP), an inhibitor of glucosylceramide synthases (Fig.…”
Section: Resultsmentioning
confidence: 93%
“…Sphingosine-induced apoptosis is associated with its conversion into ceramide by ceramide synthases [22], suggesting that the ELOVL2/DHA axis was not blocking ceramide synthase activities in beta cells. Additionally, the protective effect of the ELOVL2/DHA axis was not linked to ceramide metabolism, as the conversion of ceramide into non-toxic sphingolipids [22,25] did not affect glucolipotoxicity-induced apoptosis when ELOVL2 was upregulated. Together, these results suggest that the ELOVL2/DHA axis does not act directly on ceramide synthesis.…”
Section: Discussionmentioning
confidence: 99%